Interpreting the bone accumulations from the Sterkfontein Valley caves: a case study in quaternary research - Brain, C. K. (Southern African Humanities, 2021)
To cite this article: Brain, C.K. 1978. Interpreting the bone accumulations from the Sterkfontein Valley caves: a case study in quaternary research. Annals of the Natal Museum 23 (2): 465-8.